Global trends and risk factors of chronic kidney disease in children and young adults from 1990 to 2021: a systematic analysis of the global burden of disease study 2021 - He, Yapeng; Qian, Yan; Xu, Qiuting; Lu, Qunfeng; Zhang, Nina (Frontiers in Public Health, 2025)
IntroductionChronic kidney disease (CKD) is an important contributor to morbidity and mortality from non-communicable disease in children and young adults, but there is a lack of data on incidence, mortality, disability-adjusted life years (DALYs), risk factors, and trends in this population. This study aims to provide comprehensive estimates of the burden of CKD among children and young adults.MethodsWe conducted a trend analysis using data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021. Measures of burden at the global, sociodemographic index (SDI), and regional levels for children and young adults included incidence, mortality, and DALY rates per 100,000 population due to CKD, as well as attributable risks of death and DALYs, the annual percentage change (APC), and the average annual percentage change (AAPC). We also investigated the association between CKD burden and SDI and predicted the incidence from 2022 to 2050.ResultsGlobally, from 1990 to 2021, children with CKD demonstrated declining trends in mortality and DALYs, with AAPCs of −1.925 and −1.820, respectively; however, the incidence rate did not change significantly, although it showed a negative trend overall (AAPCs: −0.095). Conversely, all three metrics showed upward trajectories in young adults, with AAPCs of 0.941, 0.256, and 0.187. The relationship between incidence and SDI exhibited an inverse U-shaped pattern, while also demonstrating significant negative associations with mortality and DALYs. Notably, region-specific disparities emerged in attributable risk factors for mortality and DALYs among young adults. Higher SDI regions displayed greater proportional contributions from high fasting plasma glucose, high body mass index, and diets high in processed meat and red meat. Projections for 2022–2050 suggest a continued reduction in children’s CKD incidence, while projections for young adults’ incidence suggest a continued increase.ConclusionThe global burden of CKD shows divergent trends across age groups, with projected increases among young adults contrasting with projected declines among children. Lower SDI regions demonstrate a disproportionately higher burden of CKD.